PERSONAL HYGIENE DAN CEMARAN MIKROORGANISME PADA HANDPHONE MAHASISWA KESEHATAN MASYARAKAT FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Pungky Dewanti, Adek Chantika; Sujaya, I Nengah (ARCHIVE OF COMMUNITY HEALTH, 2025)
Mobile phones can be a place for more bacterial growth when compared to toilets. The growth of bacteria on cellphones can be influenced by the personal hygiene behavior of users and the ideal environment for bacterial growth, such as the temperature on cellphones. The aim of the study was to determine the effect of personal hygiene behavior and cell phone temperature on the amount of microorganism contamination on student mobile phones in the Public Health Undergraduate Study Program (PSSKM), Faculty of Medicine, Udayana University. This study used a cross-sectional field study with the Kruskall Wallis test where the sample size was 48 people. This study uses primary data through swab tests for cellphones and questionnaires to obtain information about the personal hygiene behavior of PSSKM students. The results showed that there was a relationship between personal hygiene behavior and the amount of microorganism contamination on cellphones (p = 0.009) and there was a relationship between the temperature of cellphones and the amount of microorganism contamination on cellphones (p = 0.039). Based on these results, minimizing the growth of microorganisms can be done by paying attention to personal hygiene of cellphones and oneself. Keywords: Mobile Phone Microorganisms, Swabs, Student Personal Hygiene